Age-related changes in antioxidant enzyme activities, fatty acid composition and lipid peroxidation in whole body gammarus locusta (crustacea: amphipoda) - Correia, Ana (2003)
The main aim of this work was to provide baseline data on aspects of pro-oxidant and antioxidant processes in different life-stages of the marine amphipod Gammarus locusta. The activities of antioxidant enzymes and levels of lipid peroxidation were determined in whole body juveniles, sub-adults and male and female adults of a laboratory population of G. locusta. Fatty acid composition of individuals at these different stages of development was also characterized in order to examine the contribution that polyunsaturated fatty acids (PUFA) might make to the peroxidation status of animals. The antioxidant enzymes, measured in whole body 100, 000 supernatants, comprised catalase (CAT, EC 1.11.1.6), superoxide dismutase (SOD; EC 1.15.1.1) and glutathione peroxidase (GPX; EC 1.11.1.9). Fatty acids were analyzed as fatty acid methyl esters (FAME). Lipid peroxidation was examined in terms of the levels of lipid peroxides determined as thiobarbituric acid-reactive malondialdehyde equivalents. Age-related changes were seen in antioxidant enzyme status: levels of SOD (p< 0.01) and GPX (p< 0.001) activities decreased progressively during development from juveniles to adults. Sex-related changes in GPX activity were also seen, the levels being higher in adult males than females (p< 0.001). The amount of FAME present in whole body amphipod also changed over the life span. Among PUFA, the eicosapentacenoic (C20:5n3), arachidonic (C20:4n6) and docosahexaenoic acids (C22:6n3) were the most abundant acids in this species, and both their individual concentrations and total PUFA increased progressively with age (up to 3.3-fold; p< 0.001). The latter changes may contribute to the explanation of the observed differences in peroxidation status of the animals with age; thus, levels of lipid peroxides increased up to 40 % in males compared to other age-classes (p< 0.001). Overall, the decline in antioxidant enzyme activities, coupled with increased levels of PUFA, as the individual grows older, may render the older animals more susceptible to lipid peroxidation and oxidative stress.